1979
DOI: 10.2307/2259338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grazing by a Chrysomelid Beetle, Gastrophysa Viridula, on Competition Between Rumex Obtusifolius and Rumex Crispus

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 169.230.243.252 on Tue SUMMARY(1) The effects of clipping (simulated grazing) and grazing by a chrysomelid beetle, Gastrophysa viridula, on plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
1
2

Year Published

1983
1983
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 5 publications
6
60
1
2
Order By: Relevance
“…The intensity of herbivory may also affect the H ϫ C interaction. Bentley and Whittaker (1979) only found an H ϫ C interaction at high levels of herbivory, while no interaction existed at lower levels. Both species had a significant H ϫ C interaction for mortality in this study.…”
Section: While In Two Mexicanmentioning
confidence: 74%
See 2 more Smart Citations
“…The intensity of herbivory may also affect the H ϫ C interaction. Bentley and Whittaker (1979) only found an H ϫ C interaction at high levels of herbivory, while no interaction existed at lower levels. Both species had a significant H ϫ C interaction for mortality in this study.…”
Section: While In Two Mexicanmentioning
confidence: 74%
“…In the five terrestrial studies that found no interaction between competition and herbivory, four found competition to be more important (Fowler and Rausher, 1985;Steinger and Müller-Schärer, 1992;Rees and Brown, 1992;Reader and Bonser, 1998) and the other found herbivory to be more important (Maron, 1997). Similarly, of the studies that found an interaction between competition and herbivory for growth, herbivory was more important for one (Bentley and Whittaker, 1979) and competition more important for others (Müller-Schärer, 1991;Swank and Oechel, 1991;Steinger and Müller-Schärer, 1992;Frost and Rydin, 1997). This relationship may be further complicated as the relative strength of herbivory and competition may change temporally with environmental conditions (Ang et al, 1994).…”
Section: While In Two Mexicanmentioning
confidence: 97%
See 1 more Smart Citation
“…The herbivory treatments also reduced LAR, which might result from a reduction in the quantity of foliage, but in these experiments both leaf area and leaf d, wt were not affected by the herbivory treatments. It would seem likely that R. obtusifolius allocated less of its resources into parts which were eaten by Gastrophysa, thereby increasing RS and decreasing LAR, The tendency for R. obtusifolius to allocate resources to roots in response to herbivory provides a competitive advantage over R. crispus (Bentley & Whittaker, 1979), The large root system of R. obtusifolius accounts for its persistence as a weed, plants being able to develop from root fragments and regrow from mown stumps (Weaver & Cavers, 1979;Foster, 1989), By the final harvest the changes in LAR had largely disappeared, and this might indicate that on the termination of herbivore feeding the pattern of allocation tended to return the allometry of the plant to that of the controls. Responses of this kind have been observed in grasses, Oesterheld (1992) showing that allocation towards the restoration of basic allometric ratios was a major priority regardless of the intensity of defoliation, Herbivory caused a significant decrease in SLA, Impacts of herbivory on SLA have not been covered to any degree in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion of insects also illustrates that they can alter plant competitive ability (Windle & Franz 1979;Bentley & Whittaker 1979;Bentley, Whittaker & Malloch 1980;Fowler & Rausher 1985;Cottam et al 1986;Louda et al 1990a).…”
mentioning
confidence: 99%